“An Old Song Resung and Revisited” by W. B. Yeats - Azerêdo, Genilda (ABEI Journal, 2003)
This article aims at discussing a poem by W. B. Yeats – “Down by the Salley Gardens” – by considering first the contextual surroundings of the poem, which locate it in the poetical production belonging to Yeats’s Sligo perceptions and experiences, so as to further analyse how the symmetrical formal construction of the poem camouflages conflicting ideas concerning love and life, youth and maturity, inexperience and awareness, life and art.